2009
DOI: 10.1111/j.1945-5100.2009.tb01202.x
|View full text |Cite
|
Sign up to set email alerts
|

The comparative behavior of apatite‐zircon U‐Pb systems in Apollo 14 breccias: Implications for the thermal history of the Fra Mauro Formation

Abstract: Abstract-We report secondary ion mass spectrometry (SIMS) U-Pb analyses of zircon and apatite from four breccia samples from the Apollo 14 landing site. The zircon and apatite grains occur as cogenetic minerals in lithic clasts in two of the breccias and as unrelated mineral clasts in the matrices of the other two. SIMS U-Pb analyses show that the ages of zircon grains range from 4023 ± 24 Ma to 4342 ± 5 Ma, whereas all apatite grains define an isochron corresponding to an age of 3926 ± 3 Ma. The disparity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
81
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 31 publications
10
81
0
Order By: Relevance
“…Pb, U and Th concentrations in Matrix Apatites 1-3 range from 53 to 471 ppm, 36 to 373 ppm and 44 to 298 ppm (Table 3), respectively, and have Th/U ratios in the range 0.8-1.34. U concentrations in the KREEP (apatite-rich) basaltic assemblage range from 258 to 529 ppm (average 373 ppm), which are notably higher than apatites (<212 ppm and typically <60 ppm) reported by Nemchin et al (2009) (Fig. 13) and similar Th/U ratios (12.5-13.8) suggesting that they are possibly from the same parent lithology.…”
Section: U-pb and Pb-pb Chronologymentioning
confidence: 76%
See 2 more Smart Citations
“…Pb, U and Th concentrations in Matrix Apatites 1-3 range from 53 to 471 ppm, 36 to 373 ppm and 44 to 298 ppm (Table 3), respectively, and have Th/U ratios in the range 0.8-1.34. U concentrations in the KREEP (apatite-rich) basaltic assemblage range from 258 to 529 ppm (average 373 ppm), which are notably higher than apatites (<212 ppm and typically <60 ppm) reported by Nemchin et al (2009) (Fig. 13) and similar Th/U ratios (12.5-13.8) suggesting that they are possibly from the same parent lithology.…”
Section: U-pb and Pb-pb Chronologymentioning
confidence: 76%
“…However, as has been recently demonstrated by Nemchin et al (2009), phosphates have low-closure temperatures ($500°C: Cherniak et al, 1991) that may make them more susceptible to metamorphic thermal resetting than co-existing zircon phases (see also Vaughan et al, 2006;Arai et al, 2010).…”
Section: U-pb and Pb-pb Chronologymentioning
confidence: 88%
See 1 more Smart Citation
“…Nevertheless, only a limited number of U-Pb ages of lunar phosphates are published. These published results indicate a profound resetting of the system during the 3.9 Ga cataclysm (Grange et al 2009;Nemchin et al 2009b). Rasmussen et al (2008) demonstrated that at least some lunar basalts contain a suite of Zr minerals, such as zirconolite, tranquillityite, and baddeleyite.…”
Section: U-pb Ages Of Lunar Samplesmentioning
confidence: 89%
“…Obviously there would be some delay in forming the lunar highlands to provide for accretion of the Moon after the MFI, but this is presumed to be short given the ages of the oldest lunar rocks. However, the MFI dates from about 4.5 BYBP, while the oldest lunar rocks are at least 50 MY and perhaps more than 100 MY younger (Halliday 2008;Nemchin et al 2009Nemchin et al , 2012. Figure 2.1 illustrates that this is precisely the time interval during which the late veneer would have been added to Earth.…”
Section: Chapter 4 Degassing Processes and Chemistrymentioning
confidence: 93%